Functional specialization of chloroplast vesiculation (CV) duplicated genes from soybean shows partial overlapping roles during stress-induced or natural senescence - Fleitas, Andrea Luciana; Castro, Alexandra; Blumwald, Eduardo; Vidal, Sabina (Frontiers in Plant Science, 2023)
Soybean is a globally important legume crop which is highly sensitive to drought. The identification of genes of particular relevance for drought responses provides an important basis to improve tolerance to environmental stress. Comparison of drought-induced transcriptional responses in soybean contrasting genotypes exhibiting slow-wilting (tolerant) or fast-wilting (sensitive) phenotypes enabled the identification of CV1 (Chloroplast-Vesiculation 1), whose expression profile showed a negative correlation with drought tolerance. CVs have been characterized in Arabidopsis and rice as proteins participating in a specific chloroplast-degradation vesicular pathway during natural or stress-induced leaf senescence. Like CV1, the SAG12 marker gene for senescence-associated vacuoles, was predominantly induced in fast-wilting plants. In contrast, autophagy (ATG8) and ATI-PS (ATI1) genes reached higher induction levels in slow-wilting plants, suggesting that pathways having pro-survival remobilization functions, play relevant roles in soybean drought-tolerance responses. Soybean genome contains two paralogous genes encoding highly similar CV proteins, CV1 and CV2. The biological function of soybean CVs in chloroplast degradation was confirmed by analyzing the effect of conditional overexpression of CV2-FLAG fusions on the accumulation of specific chloroplast proteins. In addition, functional specificity of CV genes was assessed by analyzing their specific promoter activities in transgenic Arabidopsis expressing GUS gene driven by CV1 or CV2 promoters. CV1 promoter responded primarily to abiotic stimuli (hyperosmolarity, salinity and oxidative stress), while the promoter of CV2 was predominantly active during natural senescence. Both promoters were highly responsive to auxin but only CV1 responded to other stress-related hormones, such as ABA, salicylic acid and methyl jasmonate. Moreover, the dark-induced expression of CV2, but not of CV1, was strongly inhibited by cytokinin, indicating similarities in the regulation of CV2 to the reported expression of Arabidopsis and rice CV genes. Finally, we report the expression of both CV1 and CV2 genes in roots of soybean and transgenic Arabidopsis, suggesting a role for the encoded proteins in N remobilization from root plastids. Together, the results indicate differential roles for CV1 and CV2 in development and in responses to environmental stress, and point to CV1 as a potential target for gene editing to improve crop performance under stress without compromising natural development.